2020
DOI: 10.1021/acs.iecr.0c02875
|View full text |Cite
|
Sign up to set email alerts
|

Double-Tube Reactor Design and Process Optimization for On-Site Steam Methane Reforming Processes

Abstract: A novel design of a double-tube steam methane reforming (SMR) reactor was evaluated in terms of conversion and reactor temperature, compared with the conventional, single-tube, fixed bed reactor. The heat from the reformate could be recovered through the double-tube reactor, which increased the conversion from 71.7 to 89.3% and lowered the reactor outlet temperature from 732.7 to 674.5 °C. An actual plant was then designed, wherein the entire operating process was tested using the doubletube reactor, which pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Therefore, conversion of the most unreactive hydrocarbon of methane under mild reaction condition is quite challenging and remains one of the globally important agendas for the development of green society 1 . Industrially, methane is utilized in the catalytic steam reforming reaction (SRM, CH4 + H2O → CO + 3H2) at high temperatures and pressures (700-1100 °C and 20-40 atm) to produce synthesis gas, a feedstock for the production of various chemical products [1][2][3] . To overcome this energy-intensive process 1,4,5 and realize on-site and ondemand methane conversion technologies for sustainable methane utilization 3 , it is indispensable to develop an effective methane activation method at ambient temperatures and pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, conversion of the most unreactive hydrocarbon of methane under mild reaction condition is quite challenging and remains one of the globally important agendas for the development of green society 1 . Industrially, methane is utilized in the catalytic steam reforming reaction (SRM, CH4 + H2O → CO + 3H2) at high temperatures and pressures (700-1100 °C and 20-40 atm) to produce synthesis gas, a feedstock for the production of various chemical products [1][2][3] . To overcome this energy-intensive process 1,4,5 and realize on-site and ondemand methane conversion technologies for sustainable methane utilization 3 , it is indispensable to develop an effective methane activation method at ambient temperatures and pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization is the process of determining the optimal solution of an objective function in the search space of a given system. Multiobjective optimization problems (MOOPs) require multiple optimal solutions, which are not easy to find owing to their conflicting objectives. Although many solution methods have been developed to solve MOOPs, multiobjective evolutionary algorithms (MOEAs) are preferable because the algorithms can maintain the solutions that are well-distributed or diverse in population at each generation without any predefined values in objective functions .…”
Section: Methodsmentioning
confidence: 99%
“…28 The mass flow rate of LNG was determined based on the assumption that the SMR process has a thermal efficiency of 81.3% and a yield of 30.4%. 28 The LNG composition derived from a published study 27 is shown in Table 3. LNG was pressurized by pump-2, passed through the C. An additional valve was installed to expand the LNG to approximately the atmospheric pressure.…”
Section: Base Case Designmentioning
confidence: 99%